Functionalizable composite nanoparticles as a dual magnetic resonance imaging/computed tomography contrast agent for medical imaging - Illert, Patrick; Wängler, Björn; Pretze, Marc; Wängler, Carmen; Zöllner, Frank G.; Uhrig, Tanja; Litau, Shanna (Journal of applied polymer science, 2019)
A dual contrast agent for computed tomography (CT) and magnetic resonance imaging (MRI) was synthesized via microemulsion polymerization. This contrast agent consists of Fe3O4 particles (d = 7 nm) with an iodine-carrying nanopolymeric shell, with overall particle sizes ranging from 50 to 250 nm. 2-Methacryloyloxyethyl(2,3,5-triiodobenzoate) was used as the monomer. Sodium oleate was used as the surfactant and its amount was varied to control the overall particle size. The composite nanoparticles were mainly characterized via dynamic light scattering, with further analyses using transmission electron microscopy and atomic force microscopy. The particles provided a highly visible contrast in CT and MR images. A template for biomedical applications was created by adding a comonomer and the particles were further functionalized with the somatostatin analogue Tyr3-octreotate. The particles were tested for specific uptake into somatostatin receptor-positive AR42J cells. The additional uptake of the functionalized particles was investigated. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47571.
Gesehen am 01.08.2019